The new gold standard 5 leadership principles for creating a legendary customer experience courtesy of the Ritz-Carlton Hotel Company - Michelli, Joseph A. (New York Mcgraw-Hill, 2008)
When it comes to refined service and exquisite hospitality, one name stands high above the rest: The Ritz-Carlton Hotel Company. With ceaseless attention to every luxurious detail, the company has set the bar for creating memorable customer experiences in world-class settings. Now, for the first time, the leadership secrets behind the company's extraordinary success are revealed.
Includes bibliographical references (p. 265-271) and index.
Keywords: Ritz-Carlton Hotels (Firm)--Management--Case studies